Integrating health promotion with and for older people - eHealth (IHOPe) – evaluating remote integrated person-centred care - Zahra Ebrahimi; Emmelie Barenfeld; Hanna Gyllensten; Patricia Olaya-Contreras; Andreas Fors; Eva Fredholm; Joanne M. Fuller; Mahboubeh Godarzi; Birgitta Krantz; Karl Swedberg; Inger Ekman (BMC Geriatrics, 2023)
Abstract Background Healthcare and welfare systems worldwide are unprepared to accommodate the growing population of older people. Simultaneously, the cost of reactive care for older people is increasing. However, healthcare systems in many countries are reforming towards integrated and person-centred care with a focus on health promotion and proactive actions. The Integrating Health Promotion with and for Older People – eHealth (IHOPe) project aims to describe and evaluate a person-centred e-support intervention that promotes a sustainable partnership between community-dwelling frail older people and health and social care professionals. Methods The IHOPe project is designed as a randomised controlled trial comparing a control group receiving standard care with an intervention group receiving standard care and add-on person-centred care through telephone support and a digital platform. The primary outcome measure is a composite score of changes in general self-efficacy and the need for unscheduled hospital care. The project is conducted in Gothenburg, Sweden. At least 220 participants aged ≥ 75 years will be included after being screened using a frailty instrument. The study design, intervention components, digital platform, and questionnaires were developed in close collaboration with an advisory group of inter-professional researchers, stakeholders, clinicians, and older representatives. Data will mainly be collected through questionnaires at baseline and 3, 6, and 12 months after inclusion in the study. Recruitment is ongoing and should be completed during 2023. Data will be analysed using quantitative and qualitative methods. The evaluation will include effectiveness, process, and health economics. The study was approved by the Regional Ethical Review Board in Gothenburg, Sweden (Dnr 2019–05364, Dnr 2020–03550, Dnr 2021–03255). Discussion The findings will expand our knowledge of remotely integrated person-centred care for frail older people. Thereby, the IHOPe project is expected to fill highlighted knowledge gaps on intervention evaluations including the triad of person-centred, digital, and integrated care elements, as well as economic evaluations of remote health services for frail older people. The study is ongoing, and the results are not completed but if they turn out to be positive, implementation is not limited to time or location. Trial registration ClinicalTrial.gov: NCT04416815. Registered 07/06/2021.